Properties of juvenile and mature woods of Hevea brasiliensis untapped and with tapping panels - Severo, Elias Taylor Durgante [UNESP]; Oliveira, E. F. [UNESP]; Sansigolo, C. A. [UNESP]; Rocha, C. D. [UNESP]; Calonego, F. W. [UNESP] (Springer, 2013)
This study was aimed at evaluating the properties of juvenile and mature wood from Hevea brasiliensis untapped and with tapping panels. Boards were taken from a 53-year-old Hevea brasiliensis plantation located in Tabapu, So Paulo, Brazil. Half of the boards had the tapping panels region, and the other half had the untapped region. The results showed that: (1) there were increases of 6.6 % in the volumetric shrinkage of mature wood when compared with juvenile wood; (2) the densities and chemical properties of juvenile and mature woods are statistically equal; and (3) the tapping panel does not influence the properties of rubberwood.